2011
DOI: 10.1038/emboj.2011.23
|View full text |Cite
|
Sign up to set email alerts
|

RNA content in the nucleolus alters p53 acetylation via MYBBP1A

Abstract: A number of external and internal insults disrupt nucleolar structure, and the resulting nucleolar stress stabilizes and activates p53. We show here that nucleolar disruption induces acetylation and accumulation of p53 without phosphorylation. We identified three nucleolar proteins, MYBBP1A, RPL5, and RPL11, involved in p53 acetylation and accumulation. MYBBP1A was tethered to the nucleolus through nucleolar RNA. When rRNA transcription was suppressed by nucleolar stress, MYBBP1A translocated to the nucleoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 103 publications
6
90
0
Order By: Relevance
“…Ribonuclease A Treatment-Ribonuclease A (RNase A) 1 treatments was performed as described (15), with slight modifications. HeLa cells were grown on millicell EZ slides (Millipore, Billerica, MA) and treated with 0.2 mg/ml RNase A. Mock treatments were performed using 0.02% Triton X-100/2 mM MgCl 2 /PBS, but without RNase A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribonuclease A Treatment-Ribonuclease A (RNase A) 1 treatments was performed as described (15), with slight modifications. HeLa cells were grown on millicell EZ slides (Millipore, Billerica, MA) and treated with 0.2 mg/ml RNase A. Mock treatments were performed using 0.02% Triton X-100/2 mM MgCl 2 /PBS, but without RNase A.…”
Section: Methodsmentioning
confidence: 99%
“…Many nucleolar proteins, such as MYBBP1A, which we have previously shown to associate with SIRT7 (8), are RNA-binding proteins (15). Therefore, we asked whether the nucleolar localization of SIRT7 and its co-localization with the Pol I complex also rely on the presence of RNA.…”
Section: Sirt7 Has An Rna-independent Nucleolar Localization and Intementioning
confidence: 99%
“…MYBBP1A, which is anchored to the nucleolus through RNA, translocates from the nucleolus to the nucleoplasm when nucleolar RNA content is reduced by inhibition of rRNA transcription. The translocated MYBBP1A acetylates and accumulates p53 by facilitating the interaction between p53 and histone acetyltransferase p300 (27). Given that nutrient shortage can reduce nucleolar RNA content by suppressing rRNA transcription, MYBBP1A may cause activation of p53 that is induced by glucose deprivation.…”
mentioning
confidence: 99%
“…8,25 Next, post-translational modification factors modify p53 to maintain its stability and activity. 8 The following factors have been identified: p300/ CBP 26 acetylates p53 to increase p53 stability and activity; SOX4 is an important p53 regulator in the cellular response to DNA damage; 6 MYBBP1A enhances the interaction between p53 and p300, which promotes p53 acetylation in response to ribosomal stress; 27 and RPL11 is required for p53 acetylation and p300 recruitment to the promoter regions of the p53 target gene in response to ribosomal stress. 28 In this study, we found that NLK binds to not only p53 but also to MDM2, and NLK stabilizes p53 by abrogating the p53-MDM2 interaction.…”
Section: Discussionmentioning
confidence: 99%